2009
DOI: 10.1063/1.3269601
|View full text |Cite
|
Sign up to set email alerts
|

Valence band offset and interface stoichiometry at epitaxial Si3N4/Si(111) heterojunctions formed by plasma nitridation

Abstract: Thermal stability of the HfO 2 ∕ SiO 2 interface for sub-0.1 μ m complementary metal-oxide-semiconductor gate oxide stacks: A valence band and quantitative core-level study by soft x-ray photoelectron spectroscopy J. Appl. Phys. 96, 6362 (2004); 10.1063/1.1809769 Measurements and calculations of the valence band offsets of SiO x / ZnS (111) and SiO x / CdTe (111) heterojunctions J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…The calculated surface density is 7.71 × 10 14 cm 2 . We obtained for bulk β-Si 3 N 4 a = 7.67Å and c/a = 0.3819, and a indirect energy gap of E g = 4.24 eV, in line with experimental and theoretical data [24,27,[40][41][42]. From the present data, we immediately note the tiny lattice mismatch (<1%) between the β-Si 3 N 4 lattice parameter and twice that of Si(111).…”
Section: Computational Techniquesupporting
confidence: 90%
See 3 more Smart Citations
“…The calculated surface density is 7.71 × 10 14 cm 2 . We obtained for bulk β-Si 3 N 4 a = 7.67Å and c/a = 0.3819, and a indirect energy gap of E g = 4.24 eV, in line with experimental and theoretical data [24,27,[40][41][42]. From the present data, we immediately note the tiny lattice mismatch (<1%) between the β-Si 3 N 4 lattice parameter and twice that of Si(111).…”
Section: Computational Techniquesupporting
confidence: 90%
“…In this respect, a feature reported in the photoemission valence band taken at 134 eV photon energy was previously ascribed to the presence of a surface state [26]. However, that intense peak at a binding energy of −1.1 eV was never measured afterwards [7,[27][28][29]. Our data also cannot support that experimental evidence mainly on two grounds: on the one hand, angular resolved photoemission is needed to highlight the tiny feature (which is hidden if integrated in all the 075303-3 Fig.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Therefore the quest of a good insulator substrate to be easily integrated into Si electronics is open. Si 3 N 4 is a good candidate to play the role of dielectric in Sibased electronic devices for several reasons, among which its mechanical strength and its large electronic band gap [20,21]. Moreover, β-Si 3 N 4 shows a tiny mismatch in lattice parameter with respect to the Si(111) plane (vide infra), and it has been demonstrated that a few layers thick β-Si 3 N 4 can be grown on top of Si(111) surfaces [22,23].…”
Section: Introductionmentioning
confidence: 99%